Development of Sex Education Model to Reduce Sexual Violence Cases in the Higher Education - Santosa, Donald Samuel Slamet; Sihombing, Lambok Hermanto (Jurnal Pendidikan Progresif, 2024)
Development of Sex Education Model to Reduce Sexual Violence Cases in the Higher Education. Objectives: Sexual violence is a strategic problem in Indonesia. According to data from the Ministry of Women's Empowerment and Child Protection, from January 1 to June 20 2023 there have been 5,053 cases. Sexual violence occurs in the world of education, including universities. The aim of this research is to develop sex education model to reduce cases of sexual violence in higher education. Methods: This research is Research and Development (R&D) which uses the ADDIE (Analyze, Design, Develop, Implementation and Evaluation) development model. The model that has been developed was tested using the Kurt Lewin technique on 30 students. The success of the model is measured using an instrument in the form of a questionnaire and analyzed descriptively. Findings: The results of this research is sex education model that has been effectively tested in reducing cases of sexual violence in higher education in the form of courses subject equivalent to 2 credits. There are several things in this model, namely learning outcomes, discussion topics and syllabus, teaching materials and resources, evaluation tools, and instructions for use. The model package that has been formed is then tested using Kurt Lewin's action research model. Conclusion: The result of this research show that this sex education model is effective in reducing cases of sexual violence in higher education. Keywords: sexual violance, sex education, higher education.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024113